Egypt’s Business Enabling Environment: An Analysis of the State’s Relevant Policies from 2018 to 2021 - Heikal, Sherif (Advances in Social Sciences Research Journal, 2023)
This article aims to provide an analysis of the government of Egypt policies with respect to business enabling environment, before the commencement of illustrating the state relevant policies; the two adopted methodological approaches which are the regulatory business environment, and the investment climate will be underscored. Several elements of regulatory business environment in Egypt are analyzed such as deregulation of business commencement, operation, and closing. And in case of business climate political stability, education policy, adequate infrastructure, and adequate health system are analyzed.